Morphology of Clapsiella magnifica gen. n., sp. n., a new hypotrichous ciliate with a curious dorsal ciliary pattern - Kuppers, Gabriela Cristina (2014)
The present work describes the morphology and infraciliature of a new hypotrichous ciliate, Clapsiella magnifica gen. n., sp. n., found in rewetted soil from a temporal pond in Argentina. It was studied by means of live observation and protargol impregnation. Its main diagnostic features are: Flexible hypotrich measuring 250–320 μm × 70–140 μm in vivo; two macronuclear nodules and 4–6 micronuclei. Single contractile vacuole. Cytoplasm transparent, cortical granules absent. Somatic ciliature composed of a tricorona of cirri, three buccal(?) cirri, 6–9 ventral rows, 3–5 right marginal(?) rows, one left marginal row, and 12–17 transverse cirri. Dorsal pattern rather complicated, with about 14 kineties and kinety fragments, with scattered kinetids among them; 17–28 caudal cirri arranged in three rows on dorsal kineties 1, 3, and 7. Remarkably, dorsal kinetids have two or four basal bodies, bearing a stiff bristle arising from left anterior basal body. Adoral zone composed of 70–92 membranelles, occupying about 40% of body length in protargol preparations; paroral and endoral curved, resembling a cyrtohymenid pattern. The peculiar dorsal ciliary arrangement and the unique combination of other characters require the establishment of a new genus for this new species, which is considered incertae sedis in the Hypotricha but possibly related to the oxytrichids.